The moderation role of self-efficacy on the relationship between transformational leadership and enjoyment in physical educational students - Sanchez García, Carolina; Reigal-Garrido, Rafael Enrique; Monteiro, Diogo; Hernández Martos, Jacobo; Hernández-Mendo, Antonio; Morales-Sánchez, Verónica Odilia (Taylor & Francis, 2025)
Background: Enjoyment in physical education classes is recognized as a key factor in fostering a positive relationship with physical activity. Its significance as a component for sports participation is emphasized. Purpose: This study investigates the moderating role of self-efficacy in the relationship between the transformational leadership of physical education teachers and students’ enjoyment during classes. The hypothesis is that students’ perceived self-efficacy moderates this relationship. Methods: An associative and explanatory approach was employed. The study involved 429 adolescents (205 boys, 224 girls) aged 14–16 from the province of Málaga, Spain. Data was collected using three questionnaires: the Transformational Teaching Questionnaire to assess the teacher's transformational leadership, the Motor Self-Efficacy Scale to measure students’ motor self-efficacy, and the Intrinsic Satisfaction in Sport Instrument to evaluate students’ enjoyment in physical education classes. Results: The findings revealed a positive relationship between teachers’ transformational leadership and students’ enjoyment in physical education classes. Moreover, students’ motor self-efficacy was found to moderate this relationship: Specifically, the positive effect of transformational leadership on enjoyment was more pronounced among students with low self-efficacy, whereas the effect was less evident among students with high self-efficacy. Discussion: The study concludes that transformational leadership influences students’ enjoyment in physical education classes, but its impact is moderated by students’ perceived self-efficacy. These results emphasize the importance of training physical education teachers in transformational leadership strategies to improve students’ experiences, fostering active and healthy lifestyles from adolescence into adulthood.
Keywords: Educación física; Enjoyment; Self-efficacy; Transformational leadership; Physical education; Adolescence